PROPOSED MARKETING STRATEGY TO INCREASE THE PERFORMANCE OF LOCAL BRAND SNEAKERS (CASE STUDY: NAH PROJECT) (The Indonesian Journal of Business Administration, 2019)
NAH Project, a local SME that engaged in sneakers industry experienced rapid business development in terms of sales and brand traction. This invites attentions to local customers including the president, Joko Widodo, which then resulted “Jokowi effect” phenomenon. However, the sales resulted inconsistent and fluctuate in high margin. Hence, this research aimed to find the causes.External and internal environmental analysis were assessed in this research to obtain SWOT and root cause analysis, which resulted that the causes are the company still rely on certain products, few channel options given to customers, and lack of marketing effort in terms of promotion.Solution strategies to be proposed are based on TOWS matrix analysis. The solutions are launch classic model sneakers, adding additional value as complimentary for consumers, strengthen customer relation for competitive advantages, adding more online marketplace, more intense promotion on social media, more detail on categorizing product, and make use of public figure endorsement. New STP and marketing mix are also added to solution strategies.The proposed strategies has its detailed actions and timeline to make the most of its implementations by start in second semester of 2019 and will be ended in the end of first semester of 2020.Keywords: footwear, marketing strategy, public figure, sneakers, social media